A influência das características da governança corporativa na gestão tributária das empresas brasileiras - Antônio Paulo Machado Gomes (2012)
The central objective of this study was to verify if the characteristics of corporate governance, such as compensation, entrenchment, board composition affect the tax management of the enterprises. For this purpose, the tax management in Brazilian companies was identified by calculating three proxies: ETR, CashETR and BTD. As a result of this first phase, it was found that Brazilian companies do not ignore the benefits of tax management, since both the ETR, and CashETR, effective rates were 25%. Moreover, we found that between 2001 and 2010 the difference between taxable income and accounting income was R$ 360 million. Another important point observed in the calculation of proxies to identify the tax management was that the year 2008 was presented the lowest effective tax rate (ETR = -23%), and the biggest difference (R$ 76 million) between taxable income and accounting profit. These events occurred due to the goodwill arising from the merger between Itaú and Unibanco and by virtue of three strategies used by companies to reduce their taxable income, which are: interest on capital (JCP), goodwill amortization and tax incentives. Thus, we can conclude that the main strategies used by companies to reduce their taxable income are the interest in capital and goodwill amortization. The tax management related to the three proxies calculated the characteristics of corporate governance was identified: (i) compensation, (ii) size of the Board of Directors, (iii) entrenchment and (iv) independence of the Board of Directors. As a result it was found that the fee may only be considered as a characteristic that influences the tax management, because only this variable was significant at a significance level of 1% in two of the three proxies calculated (ETR and BTD).